Noise-Driven Collective Behavior in Mean-Field Coupled Lorenz Oscillator Networks - Swaati Saandhya; Debarati Ghosh; A. K. Bhaskar (International Journal of Advanced Control and System Engineering, 2026)
This work investigates the spatiotemporal dynamics of an ensemble of 100 identical Lorenz oscillators coupled through a mean-field scheme in the presence of additive noise. Building on prior studies of spatiotemporal chaos in coupled Lorenz arrays and mean-field coupled chaotic oscillators, the focus is on how the competition between deterministic coupling and stochastic forcing shapes collective behavior, including complete synchronization, desynchronization, clustered states, and noise-modified spatiotemporal chaos. The governing equations are formulated for a globally coupled network with coupling in one or multiple variables, and Gaussian white noise is introduced as either common or independent forcing. Parameter scans over coupling strength and noise intensity reveal distinct dynamical regimes characterized via order parameters, space–time plots, and statistical measures. Results show that mean-field coupling alone can drive the ensemble to synchronized or oscillation- suppressed states, whereas appropriate levels of noise can both destroy and induce order by facilitating noise-induced synchronization and transitions between multistable attractors. The numerical findings are discussed in the broader context of noise-induced phenomena and chimera-like patterns in coupled chaotic oscillators and suggest directions for further analytical and experimental exploration providing valuable insights for designing robust nonlinear dynamical systems with improved stability, adaptability, resilience, and synchronization performance under uncertainty.
Keywords: Clustered states; De synchronization; Mean field coupling; Synchronization; chaos; coupled Lorenz oscillators